Foot Scan curves according to the characteristics of Zebris system Gait Analysis of the variables BioKinmatk when performing skill middle block of the Movement for the central (2-4) in Volleyball - Abedulameer, Ahmed (Journal of Physical Education, 2016)
The research aims to identify the curves of force to skill block of the Movement for the central characteristics (2-4) and find connectivity Interpersonal, use descriptive method of sample they players middle Block and dish the technical performance of the skill to extract the biomechanical variables of the characteristics of curves that provide Zebris Gait Report test which is divided into two parts first: Parameters)) variables Boikinmetek and second Butterfly Parameters)) variables Biokintek was put the results in the form of tables as it represents the ease in extraction scientific evidence and because it is appropriate to look explanatory tool and according to the data obtained for the purpose of reaching the goals of the research and verification of homework and concluded Researcher to the following conclusions, that the first payment on the podium strength be much less than the final momentum in all renderings of skill bulwark of movement, then some of the recommendations put the need to adopt trainers foundations and mechanical laws of the characteristics curves Albaiukinmetekih variables achieved skill Block of the Movement for the central (2-4) mechanical principle can be applied through mechanical tracking.